Depressive symptoms, material hardship, barriers to care, and receptivity to church-based treatment among food bank service recipients in rural Michigan. Issue 5 (2nd September 2020) - Weaver, Addie; Hahn, Rev. Jessica; Tucker, Katherine M.; Bybee, Deborah; Yugo, Katharine; Johnson, Jeffery M.; Buccalo, Nicole; Pfeiffer, Paul; Kilbourne, Amy; Himle, Joseph A.
ABSTRACT: Church-based interventions have the potential to extend services to economically disadvantaged individuals with depression in rural communities. This study examined depressive symptoms, material hardship, barriers to mental health treatment, and perceptions of a church-based group depression intervention among a sample of 57 rural residents seeking food-bank services. Forty-nine percent of respondents screened positive for depression on the Patient Health Questionnaire-2. Respondents with positive depression screens (M = 2.22; SD  = 1.74) experienced greater material hardship compared to non-depressed respondents (M = 1.21; SD  = 1.00; U = 262.0; p =.04). The most commonly endorsed barriers to mental health treatment were: cost (47.4%), lack of transportation (31.6%), no insurance/lack of insurance coverage (26.3%), and wanting to handle these problems on my own (26.3%). The majority of respondents indicated that church-based depression treatment would benefit their community (62.5%), would consider attending church-based depression treatment (55.4%), and would recommend this intervention to others experiencing depressive symptoms (66.1%). Clinical and policy implications of these findings are discussed.